Twilight : the graphic novel. Volume 1 - Meyer, Stephenie, 1973- (Meyer, Stephenie, 1973- Twilight saga, 2010)
"When Isabella Swan moves to the gloomy town of Forks and meets the mysterious, alluring Edward Cullen, her life takes a thrilling and terrifying turn. With his porcelain skin, golden eyes, mesmerizing voice, and supernatural gifts, Edward is both irresistible and impenetrable. Up until now, he has managed to keep his true identity hidden, but Bella is determined to uncover his dark secret"--Dust jacket flap.